The Theory of Citizenship as a Medium in Promoting Public Policy - Patma Tuasikal; Andre Paulus Saleky (Penerbit STKIP PGRI Bangkalan, 2018)
This study was aimed to find a theory about the study of civic education developed asa medium in promoting the public policy. This study used a qualitative approach, withthe type of library research to explore liberal, communitarian and republicantheories, with data sources consisting of textbooks, journals, and magazines withcriteria of relevancy principles relating to research. While the technique of datacollection using focused study, with primary source method is Th. Marshall andsecondary sources of Peter H. Schuck, Pettit and Thomas Janoski & Brian Gran. Thisstudy showed that the theory of civic education on the concept of communitarianrepublican was very appropriate in promoting public policy, while liberal theory onlyleads to political democracy about the freedom to express opinions; however otherelements were not appropriate because of it against the values of Pancasila.